J.G.A. Pocock and the idea of the 'Cambridge School' in the history of political thought. Issue 1 (2nd January 2019) - James, Samuel
ABSTRACT: This article offers a reinterpretation of the origins and character of the so-called 'Cambridge School' in the history of political thought by reconstructing the intellectual background to J.G.A. Pocock's 1962 essay 'The History of Political Thought: A Methodological Enquiry', typically regarded as the first statement of a 'Cambridge' approach. I argue that neither linguistic philosophy nor the celebrated work of Peter Laslett exerted a major influence on Pocock's work between 1948 and 1962. Instead, I emphasise the importance of Pocock's interest in the history of historiography and of his doctoral supervisor, Herbert Butterfield. By placing Pocock's intellectual development in these contexts, I suggest, the autonomy of diverse versions of the 'Cambridge' approach can more readily be perceived.